A luminous X-ray outburst from an intermediate-mass black hole in an off-centre star cluster. (August 2018) - Lin, Dacheng; Strader, Jay; Carrasco, Eleazar; Page, Dany; Romanowsky, Aaron; Homan, Jeroen; Irwin, Jimmy; Remillard, Ronald; Godet, Olivier; Webb, Natalie; Baumgardt, Holger; Wijnands, Rudy; et al.
Abstract A unique signature for the presence of massive black holes in very dense stellar regions is occasional giant-amplitude outbursts of multi-wavelength radiation from tidal disruption and subsequent accretion of stars that make a close approach to the black holes1 . Previous strong tidal disruption event (TDE) candidates were all associated with the centres of largely isolated galaxies2–6 . Here, we report the discovery of a luminous X-ray outburst from a massive star cluster at a projected distance of 12.5 kpc from the centre of a large lenticular galaxy. The luminosity peaked at 1043 erg s−1 and decayed systematically over 10 years, approximately following a trend that supports the identification of the event as a TDE. The X-ray spectra were all very soft, with emission confined to be ≲3.0 keV, and could be described with a standard thermal disk. The disk cooled significantly as the luminosity decreased—a key thermal-state signature often observed in accreting stellar-mass black holes. This thermal-state signature, coupled with very high luminosities, ultrasoft X-ray spectra and the characteristic power-law evolution of the light curve, provides strong evidence that the source contains an intermediate-mass black hole with a mass tens of thousand times that of the solar mass. This event demonstrates that one of the most effective means of detecting intermediate-mass black holes is through X-ray flares from TDEs in star clusters. A bright X-ray outburst from a massive star cluster 12.5 kpc from a galactic centre fits the profile of a tidal disruption event (TDE), indicating the likely presence of an intermediate-mass black hole (IMBH). TDEs could be the most effective way of identifying IMBHs.